Analisis Curse Theory pada Sumber Daya Alam Migas Bagi Warga Madura - Hidayaturrahman, Mohammad (IAIN Palangka Raya, 2018)
Government policies in natural resource management, especially in the oil and gas sector face a lot of problems. However, the government also has a responsibility to improve the life of people affected from oil and gas exploration and production activities. This research was aimed at investigating how the implementation of policies run by the central and local government toward the oil and gas management and community empowerment, especially the community located closely